Childhood trauma in individuals who experience the criminal justice system: an exploration of the role of early maladaptive schemas and the benefits of psychological interventions - Antonini, Carolina E (2022)
The association between childhood trauma and offending behaviour is well established and the identification of factors that may explain this relationship is vital to elucidate causal links and ultimately, inform clinical practice. This thesis is concerned with psychological factors that may account for the relationship between early trauma and harmful behaviour, with a focus on the benefits of psychological and organizational interventions for traumatised forensic populations. A range of methods were used to explore this. An empirical study investigates the role of Early Maladaptive Schemas (EMSs) in mediating the relationship between childhood trauma and violent behaviour. A systematic review investigates the benefits of Schema Therapy (ST) informed interventions with forensic populations. A second study implements and evaluates an organizational intervention, based on Trauma Informed Care principles, for staff working with adults with histories of trauma and offending, in community settings. Finally, a critical evaluation of the Adverse Childhood Experiences questionnaire (ACE) explores its psychometric properties and discusses its use in research and clinical practice. Results of the first study found that elevated EMSs scores mediated the relationship between childhood trauma and violent convictions. Moreover, when schema domains were examined, it was found that disconnection/rejection was the only domain that mediated this relationship. In addition, there were strong positive correlations between most schema domains and violent behaviour. The systematic review provided a degree of support for the benefits ST interventions. However, the evidence mainly concerns correlates of offending and is limited to male samples within secure settings, thus restricting the generalisation of findings. Results of the second study found positive intervention effects for incidents involving sexual harassment, hate speech, and verbal abuse towards staff. The evaluation of the ACE indicated that it holds acceptable psychometric properties; nevertheless, further evidence is needed. Additionally, the ACE is better suited for epidemiological studies, and it is not recommended for use in clinical practice. The thesis concludes that more research is needed to better understand the mediating role of EMS and how different interventions may be of benefit to traumatised forensic populations.